Islamic Guidance on Resolving Marital Discord: A Critical Analysis - Sabbir Hasan Sabbir (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2023)
Humans are social beings. Society does not develop without family ties. Islam has given special importance to the formation of a family-centred society. According to Islam, the purpose of marriage is not only to fulfil biological needs; rather, marriage is a sacred relationship with mutual responsibility, respect, love, and sincerity. Marriage contributes to the creation of a family between a man and a woman. Similarly, in married life, love creates affection between each other and binds the bond of dignified living and peaceful harmony. Husband and wife complement each other in family life. Both husband and wife come from two different families to form a family. As life goes on, both of them have some misunderstandings. Small mistakes lead to big mistakes. If these mistakes are not corrected, marital discord begins. Due to marital discord, the abode of happiness called family once turned into hell. This conflict goes to a serious level and sometimes becomes life-threatening. Islam urges the maintenance of marital relations until the end of life, and to that end, it prescribes patience, tolerance, and responsible behavior. In this research, the causes that are responsible for marital discord have been revealed, and an attempt has been made to determine what the husband and wife should do by searching for a clear solution in the light of Islamic Shari'ah.